Between/beyond the binaries: transgender youth in cape town re-present their experiences through photo-narratives - Pitcher, Sorrel Claire (Department of Psychology, 2019)
Current literature about marginalised youth centres adult knowledges and perpetuates narratives of risk. Additionally, very little is known about young transgender persons within the South African context. Therefore, by making use of Photovoice elements, this narrative project sought to explore the lived experiences of transgender youth while simultaneously creating a space where they could discuss and re-present these experiences. The project aimed to challenge dominant narratives about transgender youth; youth gender and sexuality, and to expand transgender research in South Africa. This project also aimed to contribute to the empowerment of participants by positioning them as experts and centring their knowledges. The study was conducted in partnership with an LGBTIQ+ advocacy NGO and purposive sampling was used to recruit five trans-identifying participants between the ages of 18-26. In-depth interviews were conducted around what it means to be a young transgender person in Cape Town today, and the photographs participants took to represent these experiences. All data were analysed using thematic narrative analysis. The overarching thematic narratives that emerged were: ‘Navigating Identities’ and ‘Living within/out the Cistem’. Within these themes, participants drew on narratives of rigidity/fluidity, exclusion/belonging, and invisibility/hypervisibility respectively. The findings illustrate the complexity of experiences of transgender youth and thus demonstrates that young peoples’ lives are comprised of more than inherent risk. This project also provided an opportunity to critically reflect on Photovoice as a methodology for working with marginalised groups.